The effects of the Covid-19 Pandemic on the transition towards digital health solutions: evidence from telemedicine use in Germany - Baba, Daiki (2021)
Purpose – The purpose of this thesis is to examine the effects of the COVID-19 pandemic on telemedicine and the acceptance and use of this service by physicians in Germany. Design/Methodology/Approach – The research consists of several expert interviews and an online survey among physicians in Germany. Country-specific characteristics of the German healthcare system are described, and physicians’ perceptions of the benefits and limitations of telemedicine are elaborated. Findings – The results indicate that both, the acceptance and use of telemedicine among German physicians have increased in the wake of the COVID-19 pandemic. Nevertheless, it is evident that telemedicine is only used in specific cases and that the service is currently merely a complement to traditional healthcare. The main benefits of telemedicine are the savings in travel time for physicians and patients as well as improved interactions between physicians, while the main limitations are technical difficulties and the lack of physical patient examinations. Physicians from university hospitals, who are young and have strong technological know-how are the main users of telemedicine in Germany. Practical implications – The perspective of physicians provides insights for managers who develop, sell, and implement telemedicine solutions as well as for decision makers who establish telemedicine in medical institutions. Originality – This thesis aims to contribute to the scientific literature by analyzing the effects of the COVID- 19 pandemic on the adoption of telemedicine by physicians in Germany as existing literature mostly relates to patients.